Analisis Perancangan Pembelajaran Dalam Pelatihan Keterampilan Pembuatan Sovenir Bagi Karang Taruna - Aswan, Dedy (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to develop a well-structured and flexible training program for Karang Taruna members interested in developing souvenir-making skills. A comprehensive survey was conducted to identify the preferences and needs of the participants. The survey results indicated that the most favored types of souvenirs are keychains, custom-designed shirts, handbags, and accessories. Practical sessions led by experts and the use of local materials were identified as the most appealing training elements for the participants. A blended learning approach, combining online and in-person training, was identified as the most suitable method to accommodate the busy schedules of the members. Additionally, a curriculum that includes entrepreneurial skills such as business planning and marketing strategies was deemed essential to equip participants with the necessary tools for business success. This study emphasizes the importance of a well-designed training program to empower Karang Taruna members, enhancing their skills, creativity, and entrepreneurship. The program is expected to contribute to the economic development and self-sufficiency of the community, creating a sustainable positive impact on the broader socio-economic landscape.